Obóz . niezależne pismo poświęcone problemom krajów ościennych, no. 4, 1982 - Ananicz, Andrzej; Maziarski, Wojciech; Korlak, Zbigniew; Jarocińska, Sławomira (Spółka Wydawnicza Przyszłość, 1982)
Creation and circulation: From issue no. 19(1990) published legally